Appropriation of Information and Communication Technologies in The Venezuelan Education - Marcano-Rojas, Ingrith Roselys (2014)
The purpose of this research is to evaluate the use of information and communication technology as a means to support teacher training in Venezuela, specifying how the technological intervention has been taken in the educational environment. This is a documentary work that makes mention to experiences of some countries such as Panama, Colombia, Mexico and Argentina in relation to the use of ICT in education, comparing them with national effort, emphasizing out that in Venezuela, the resources have been earmarked, and some projects have been created in order to improve the quality of education, especially in the field of information and communication technologies, likewise, many projects have emerged from the national level, that are directed to the attention of general community to computer use and communications, for this reason, projects like the National Plan for Technological Literacy (PNAT), and Web portals of distance learning were created. Finally, it concludes that the efforts should be concentrated to contribute the fortification of teacher training in our country, taking into account the great potential that the nation has to support its technology plans, considering the number of students in higher education who are willing to serve communities in their educational area. So that, it is time to undertake a meaningful work with volunteer students from community service, in order to share their knowledge in the preparation of teachers in training or in exercise, being this a proposal in favor of strengthening collaborative work between educational institutions.